ENERGY EXCHANGE AND TRANSDUCTION PROCESSES IN BIOMOLECULES - Maxsudov Valijon; Arzikulov Fazliddin (American Journals Publishing, 2025)
Energy exchange and transduction are fundamental processes in biomolecules that sustain life at the cellular level. These processes involve the conversion of energy from one form to another, enabling biochemical reactions, signal transmission, and mechanical work within cells. This article reviews the mechanisms by which biomolecules such as proteins, enzymes, and nucleic acids participate in energy transfer and transformation. Emphasis is placed on key processes including ATP synthesis, electron transport chains, and molecular motors. Additionally, the role of conformational changes and allosteric regulation in energy transduction is discussed. Understanding these molecular mechanisms provides insights into cellular metabolism, bioenergetics, and has implications for the development of biomedical and nanotechnological applications.
Keywords: Energy exchange, energy transduction, biomolecules, ATP synthesis, electron transport chain, molecular motors, bioenergetics, conformational changes, allosteric regulation, cellular metabolism.